Socialization of Fintech and Product Branding for Bina Cipta High School Students - Dwi Maharani; Dewi Sartika; Desi Misnawati; Sabeli Alya; Afriyudi (Jurnal Pengabdian Pancasila (JPP), 2022)
The purpose of community service activities is to increase knowledge about fintech and product branding for Bina Cipta High School students. The method used socialization through planning, implementation and evaluation. Data collection techniques using a questionnaire. Quantitative data analysis. Subjects amounted to 30 people. The results of community service showed an 83% increase in knowledge about fintech and product branding for Bina Cipta High School students consisting of material 1) media socialization of healthy living among students, 2) fintech and opportunities, 3) product branding in the media, 4) fintech applications in Indonesia, 5) the concept of fintech.